Asuhan Keperawatan Anak Dengan Asma Bronkial Di Ruang Rawat Inap Anak Rsud Prof. H. M. Yamin, Sh.Pariaman Tahun 2026 - Octaviona Putri; Reska Handayani; Prima Yoselina; ErpitaYanti . (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Bronchial asthma is a chronic disease of the respiratory tract characterized by inflammation and narrowing of the airways, causing shortness of breath, chest tightness, coughing, and wheezing. Data from the pediatric inpatient ward at RSUD Prof. H. M. Yamin, S.H. Pariaman showed an increase in cases from 37 in 2023 to 117 in 2024, and in 2025 it ranked 7th among the top 10 most common diseases with 61 cases. This study aims to provide direct nursing care to patients with bronchial asthma through the stages of assessment, diagnosis, intervention, implementation, and evaluation. The study was conducted from February 11 to 15, 2026, in the pediatric inpatient ward using a case study approach on one patient, A.n S, aged 5 years. The assessment results identified four nursing diagnoses: ineffective airway clearance, ineffective breathing pattern, sleep pattern disturbance, and risk of nutritional deficit. Interventions included monitoring breathing patterns and respiratory rate, monitoring food intake, and identifying factors that disturb sleep. The evaluation showed that sleep pattern disturbance and ineffective breathing pattern were resolved on the fourth day, while ineffective airway clearance and risk of nutritional deficit were resolved on the fifth day.This paper is expected to serve as a reference for healthcare professionals to improve their skills in providing nursing care for children with bronchial asthma. Parents are expected to pay closer attention to their child’s health through proper home management, such as maintaining good ventilation, ensuring medication adherence, avoiding triggers like cigarette smoke, and recognizing early signs of recurrence.